Vegetation and Colonization Status of Mycorrhizal and Endophytic Fungi in Plant Species on Acidic Barren at Crater Basin of Volcano Esan in Hokkaido, Japan - Fukuchi, Souta; Obase, Keisuke; Tamai, Yutaka; Yajima, Takashi; Miyamoto, Toshizumi
We investigated the colonization status of mycorrhizal and endophytic fungi in roots of plants established on an acidic barren at volcano Esan, Hokkaido, Japan. In total, 87 individuals of 21 plant taxa were investigated in four different vegetation sites and the surrounding area. Ericaceous plants such as Empetrum nigrum var. japonicum, Ledum palustre var. diversipilosum, Vaccinium vitis-idaea var. minus and Loiseleuria procumbens were the main colonizers at the study sites and dominated under even the most severe conditions of low soil moisture and nutrient content. They were associated with ericoid mycorrhizal (ERM) fungi at all vegetation sites and erratically with dark septate endophytic (DSE) fungi. They commonly associated together with arbuscular mycorrhizal (AM) fungi only at sites where Sasa senanensis dominated. Among the ericaceous plants, only Enkianthus campanulatus associated with AM and DSE fungi and had no associations with ERM fungi. Other herbaceous and woody plants associated commonly with AM or erratically with DSE fungi, except for Carex sp. and Polygonum spp. which erratically associated with AM and DSE fungi. Mycorrhizal associations were common in representative vegetation on the crater basin of Mt. Esan. In particular, ERM associations might play a significant role in invasion and establishment of ericaceous plants, and also in the development of plant communities in the harsh environment at Mt. Esan.